Estimating the opportunity costs of environmental conservation in the Feijão River watershed (São Carlos-SP, Brazil) - Machado,F. H. (2016)
Abstract The objective of this study was to infer the opportunity cost of land use of the Feijão River watershed (São Carlos-SP, Brazil), in order to estimate the financial resources necessary to compensate landowners willing to convert their production areas into areas of environmental preservation. Net values were estimated by calculating the Annual Value and the Net Present Value of each activity. The area used for agricultural production was estimated using the Land Cover Map of the watershed. The study involved four production areas: forestry, livestock, sugarcane and orange, accounting for 66% of the watershed area of 22,300 hectares. Considering a scenario of total consent from landowners, the 2011 net annual values were estimated at R$ 13.4 million: R$ 2.2 million (eucalyptus), R$ 1.9 million (livestock), R$ 1.1 million (sugarcane) and R$ 8.2 million (orange). This amount would be used as payment for ecosystem services.